KAJIAN TEORI ANDROGINI TERHADAP JENIS PERMAINAN DALAM PEMAHAMAN KARAKTER GENDER ANAK - Zaifullah, Zaifullah (Musawa: Journal for Gender Studies, 2019)
His paper is a literature review to explain the Androgyny theory of types of games in shaping the understanding of children's gender roles. The androgyny theory is expected to be able to change people's views about people's understanding of gender and gender which is very influential in the selection of games for young children so that it is considered very important to understand the difference between sex and gender.